Effective occupational health and safety performance measurements - Jafri, Hasnora; Ali, Mohamad Wijayanuddin; Ahmad, Arshad; Kamsah, Mohd. Zaki (2005)
Achieving excellent OHS performance involves more than avoiding injuries, ill health and accident. However measurement of occupational health and safety (OHS) performance is not easy to construct due to the various dimensions being measured and the dynamic nature of OHS issues. Most organization measure OHS performance statistically by the number of accidents, days lost, injury rates and accident costs. Statistical methods may indicate the nature, frequency and severity of injury, or may identified the problem areas but they are not sufficient measurement tools as they reveal OHS performance in the past and do not reflect the current status of OHS management nor predict the possible occurrence of accident and there are also problems of incorrect or underreporting. Organizations must identify and use other measures that reflect the organizations true initiatives and behaviors, which promote well being and safe performance. Proactive OHS metrics may include behavior-based indicators, safety culture, management involvement, employee empowerment, employee perception survey, safety audits and root cause analysis. These measurements when use together with accident and injury rates statistics will indicate the overall performance of OHS and give directions for OHS management improvement. This paper looks at performance measurement system for OHS improvement. A literature review on effective OHS performance measurement is presented and a framework for OHS performance measurement is described and followed by a discussion on the use of other metrics that motivate change rather than describe past performance of occupational health and safety management.